2021
DOI: 10.1186/s12889-021-11025-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of chicken management practices in children’s exposure to environmental contamination: a mixed-methods analysis

Abstract: Background Household chicken production presents an opportunity to promote child nutrition, but the benefits might be offset by increased environmental contamination. Using household surveys, direct observations, and in-depth interviews with woman caregivers, we sought to describe the relationship between chicken management practices and household exposure to environmental contamination, and assess barriers to adopting improved husbandry practices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Chickens are important reservoirs of Campylobacter bacteria that cause enteric infection in children. Studies reported an association between poultry keeping with stunting highlighting the importance of keeping chickens in separate shelters or cages [ 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chickens are important reservoirs of Campylobacter bacteria that cause enteric infection in children. Studies reported an association between poultry keeping with stunting highlighting the importance of keeping chickens in separate shelters or cages [ 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In EED, nutrients are poorly absorbed due to atrophied villi and lost due to increased intestinal permeability (leaky gut) [ 25 ]. Thus, poultry interventions that aim increased egg intake and improved health and nutrition status should consider strategies to reduce disease transmission from chickens to children [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four interventions focused on the use of child-safe spaces [ 22 , 30 , 33 , 36 ], two interventions focused on managing cohabitation between humans and animals by encouraging building of animal hutches/coops [ 31 , 35 ] and two educational interventions encouraged appropriate removal of faeces from the household environment [ 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies focussed on managing the cohabitation of livestock with humans. Passarelli et al [ 35 ] conducted a study in Ethiopia using a cluster randomised trial, dubbed “Agriculture-to-Nutrition” (ATONU). The objective of the larger study was to evaluate the impact of integrating nutrition-sensitive behavioural change communication in the context of increased household production of chickens and eggs on the diets of women and children.…”
Section: Resultsmentioning
confidence: 99%
“…However, achieving improvements in practices is also not a given without additional support, particularly in a context where financial constraints are binding and improving practices requires financial investment. To some degree, this was the case with corralling poultry in Burkina Faso, where poultry corralling was associated with increased costs of production related to the coop itself but also with regard to feed necessary to compensate for lack of scavenging opportunities for free‐roaming poultry (Leight, Awonon, Pedehombga, Ganaba, Gelli, 2022 ; Passarelli et al, 2021 ). Providing some form of transfer to encourage households to invest in improved poultry housing could be considered by programme implementers as a way to enhance potential effectiveness and avoid unintended effects (Alderman et al, 2022 ; Gelli et al, 2018 ; Olney et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%